PARTISIPASI PEMUDA DALAM MENYUKSESKAN PROGRAM PNPM MANDIRI PERDESAAN DI DESA BULUROTO KABUPATEN BLORA - Bayu Adhi Nugroho; Kushandajani .; Puji Astuti (Journal of Politic and Government Studies, 2015)
In terms of rural development, community participation is essential to increase the community’s life quality and welfare. Youth generation, as the agent of change, has major rule in the empowerment since they have pure motivation to develop their area. The Community Empowerment Program in Rural Areas (PNPM Mandiri Perdesaan/PNPM-MD) had facilitated the development program in Buluroto Area from 2009 to 2014. From that background, this undergraduate thesis discussed the research question: “How the youth in Buluroto Village participated in the Community Empowerment Program in Rural Areas (PNPM Mandiri Perdesaan/PNPM-MD)? and What were the obstacles faced by the youth during the implementation of the Community Empowerment Program in Rural Areas (PNPM Mandiri Perdesaan/PNPM-MD) in Buluroto Village?The research used descriptive-qualitative method using the samples obtained based on purposive sample method that was designed by the author and conducted by performing in-depth interview, observation, and documentation. The data were then analyzed by data reduction, data presentation, and making conclusion.The result showed that the level of youth participation in planning process, implementation, monitoring and evaluation as well as implementation of the program was low, while the youth participated well enough in maintaining the outcome of the program. The obstacles during the planning process were less dissemination from the village administration and no youth organization. During the program implementation, the obstacle was that the program was done completely by contractors so that in monitoring and evaluating process, the youth had no chance to monitor and give input related to the problems occurred during the implementation. While in maintenance stage, the obstacles were less information related to SPP and strict selection from the village administration and the implementation team. The village administration is suggested to givemore information to the youth about the development of the area, while the youth is suggested to be more proactive and care about the development in Buluroto Village.Key words: Youth, participation, empowerment.